Research data management: production and impact from Dimensions database data - Andrade Gontijo, Marília Catarina; Hamanaka, Raíssa Yuri; Ferreira de Araújo, Ronaldo (Advanced Notes in Information Science, 2022)
The study aims to analyze the scientific production of research data management indexed in Dimensions. Using the term “research data management”, 677 articles were retrieved and analyzed using output and citation bibliometric indicators. The multidisciplinary in research data management was demonstrated by publications occurring in different research areas, such as computer science, information systems, library and information science, medicine and health sciences, and history and archeology. The countries with the highest publication rates were the United States, Germany, and the United Kingdom. About 60% of the publications had at least one citation, with 3,598 citations found, featuring a growing academic impact since the volume of production and citations have grown over time. When it comes to the Big Data era, data management is a topic under development that ensures its sharing and reuse and, consequently, the advancement of science. This bibliometric study made it possible to monitor the literature performance on research data management.